The Effect of Reading Aloud on the Students’ Ability in Reading Comprehension - Efrini Panjaitan; Kartina Rahmadhani Rambe; Rafita Tioria Sianipar; Samaria Eva Elita Girsang; Linda Ramadhani (LingPoet: Journal of Linguistics and Literary Research, 2023)
This study focuses on an experimental study design to investigate the effect of reading aloud strategy on students' comprehension when reading narrative texts. Reading aloud is an activity to read something important in reading, such as helping students read language items better and helping them practice word stress, intonation, and pronunciation. 60 SMA Swasta Melati Binjai tenth graders in the 2022/2023 school year were selected as the subjects of the study. Besides, the read test tool is analyzed as valid by looking at the t-counted coefficient (4.635) greater than the t-table factor (1.70113) and it is also analyzed as reliable by looking at the confidence factor (0.763) higher than the panel coefficient (0.3061); this is also shown by t-test analysis that the coefficient is high and significant by considering that the countable coefficient (3.219) is larger than the testable coefficient (1.70113). This means that there is an effect of reading aloud strategy on a student's ability to understand the text. Therefore, the research hypothesis is accepted.